2010
DOI: 10.1002/poc.1618
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable emissions in diprotonated 2,2′:6′,2″‐terpyridine derivatives

Abstract: A series of new metal‐free blue emission compounds, i.e., diprotonated terpyH2ClPF6 (1), tterpyH2ClPF6 (2), ClterpyH2ClPF6 (3), and BterpyH2(PF6)2 (4), were prepared and characterized by electrospray ionization mass spectrometry, UV–vis spectroscopy, and cyclic voltammetry (CV). Abbreviations used are terpy = 2,2′:6′,2″‐terpyridine, tterpy = 4′‐(4‐tolyl)‐2,2′:6′,2″‐terpyridine, Clterpy = 4′‐chloro‐2,2′:6′,2″‐terpyridine, and Bterpy = 4,4′,4″‐tert‐butyl‐2,2′:6′,2″‐terpyridine. The X‐ray crystal structures of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 35 publications
(44 reference statements)
3
22
0
Order By: Relevance
“…The fluorescence of the ddpd ligand shifts to higher energy through protonation in CH 3 CN, whereas the protonation of tpy leads to a redshifted emission from λ = 340 to 412 nm (and to 395 nm upon further protonation) in this solvent . This opposite behavior can probably be attributed to the different protonation sites.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The fluorescence of the ddpd ligand shifts to higher energy through protonation in CH 3 CN, whereas the protonation of tpy leads to a redshifted emission from λ = 340 to 412 nm (and to 395 nm upon further protonation) in this solvent . This opposite behavior can probably be attributed to the different protonation sites.…”
Section: Resultsmentioning
confidence: 98%
“…This opposite behavior can probably be attributed to the different protonation sites. Although tpy can only be protonated at the pyridine rings, which increases their acceptor strengths,[13c] the NR 3 moieties of ddpd should be more basic than the pyridine rings. For example, the p K a value of pyridinium ions [p K a (Hpy + ) = 5.3] is much lower than that of protonated 4‐dimethylaminopyridine [HDMAP + , p K a (HDMAP + ) = 9.6] .…”
Section: Resultsmentioning
confidence: 99%
“…31 Diprotonation results in a further increase in QY. 31 Diprotonation results in a further increase in QY.…”
Section: Solid-state Photoluminescencementioning
confidence: 99%
“…The blue fluorescent 4′‐(4‐methylphenyl)‐terpy is known as an electron transport and electroluminescent material to design emitting diode (OLED) applications . Recently, it has been reported that monoprotonated terpyridine cation ([terpyH] + ) indicates stronger emission in acetonitrile than that of the parent neutral species (terpy) . Preparation and investigation of the diprotonated terpyridine cation ([terpyH 2 ] 2+ ) has also been reported …”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Preparation and investigation of the diprotonated terpyridine cation ([terpyH 2 ] 2 + ) has also been reported. [14][15][16][17][18][19][20] In this work, we report new intense emission compounds that possess hydrogen bond between [terpyH 2 ] 2 + and PF 6 À in the compounds. Eleven compounds and their structures were examined using DFT calculation: [(terpyH 3 )F](PF 6 ) 2 (1F), [(ter-pyH 3 )Cl](PF 6 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%